Eophyll and cotyledon structure of four types of seedlings from the Restinga Forest, Paraná. - Cavichiolo, Letícia Estela (2009)
Seedlings represent one of the most fragile stages in the life cycle of plants and they depend on morpho-functional adaptations which may favor their establishment in adverse environmental conditions. We analyzed the eophyllar and cotyledonar anatomy of four seedling types in the Restinga Forest, Ilha do Mel, Paraná, (PEF: Ilex pseudobuxus-Aquifoliaceae; PER: Tapirira guianensis-Anacardiaceae; CHR: Ocotea pulchella-Lauraceae; CER: Faramea marginata-Rubiaceae) to investigate the relationships between the anatomical structure and function. Eophylls of PER, CER and CHR seedlings are structurally similar to true leaves of adult individuals and structurally more complex than cotyledons. This could explain the higher abundance of photosynthetic seedlings in high light environments and reserve’s seedlings in shaded environments in the tropical communities.